An Investigation of the Relationship between English Language Proficiency and Information Technology Literacy - Yamat @ Ahmad, Hamidah (2001)
Today's dependence on technology has changed how we view literacy. Literacy no longer means to have only the ability to read and write. Literate people now must be able to use the computer and other communication technologies in handling the vast information. In conjunction with this, there is a need to study what is meant by Information Technology (IT) literacy and what is required to be IT literate. This study was based on the belief that proficiency in the language of technology, that is the English language, would enhance IT literacy. Hence, the relationship between two variables, English language proficiency and IT literacy, was studied. Proficiency was identified through students' scores in the SPM English examination while IT literacy was identified through the IT proficiency questionnaire. Other contributing factors to IT literacy were also discussed. 257 second year UPM students from five different faculties provided the qualitative and quantitative data for this study. They were given a set of questionnaire to respond to and were briefly interviewed for further insights. Data were then analysed. Both descriptive qualitative and quantitative analyses provided the answer to the five research questions that motivated the study. Subject to the limitations of the study, the results showed a significant relationship between English language proficiency and IT literacy. In other words, proficiency in the English language tends to enhance IT literacy. This is because IT literacy requires the skill to use computers and other communication technologies. This skill can be acquired through hands-on experience and exploration which requires a profound proficiency level of the language of technology, that is the English language. Hence, one must be proficient in the English language to be IT literate.